Effect of chronic alcohol consumption on the development and progression of non-alcoholic fatty liver disease (NAFLD) - Seitz, Helmut K.; Mueller, Sebastian; Hellerbrand, Claus; Liangpunsakul, Suthat (Hepatobiliary surgery and nutrition, 2015)
A number of epidemiologic studies show a protective effect of light to moderate daily alcohol consumption on the development of non-alcoholic fatty liver disease (NAFLD). Although these small amounts of ethanol may prevent fatty liver, they may also be a risk factor for other diseases such as breast and colon cancer. Those individuals who have underlying hepatic steatosis or non-alcoholic steatohepatitis (NASH) should not use ethanol chronically since the data available at present do not support a beneficial effect of alcohol in this situation. Especially overweight and obese individuals may be more susceptible towards alcohol even at moderate doses. Animal experiments show a negative effect of ethanol on liver histology in either dietary or genetic NASH models. In addition, patients with NASH reveal a significant increased risk for hepatocellular cancer (HCC) even with social alcohol consumption. Thus, subjects with underlying NASH should abstain from alcohol at any amounts.
Gesehen am 16.06.2020